UPAYA NON PENAL PENANGGULANGAN TINDAK PIDANA KORUPSI OLEH KOMISI PEMBERANTASAN KORUPSI REPUBLIK INDONESIA PERIODE 2012-2015 - Safik Faozi; Wenny Megawati; Dyah Listyarini (Universitas Stikubank, 2023)
Non-penal efforts are one of the efforts to tackle crime, including corruption crimes. The purpose of this study is to explain the KPK's non-penal efforts to tackle corruption. The method used is literature study with primary and secondary law materials. The result is that KPK's non-penal efforts are prevention efforts that complement efforts to eradicate corruption. The form of using the mass media to form public opinion about the consequences of corruption and criminal sanctions. In addition, it also encourages the formation of national mental health in state and government institutions, community organizations, political parties, the involvement of community organizations and universities in tackling corruption crimes. Keywords: Non-penal efforts, KPK, Corruption.